Alkane Oxidation by an Immobilized Nickel Complex Catalyst: Structural and Reactivity Differences Induced by Surface‐Ligand Density on Mesoporous Silica. Issue 6 (12th April 2013) - Nakazawa, Jun; Hori, Tomoaki; Stack, T. Daniel P.; Hikichi, Shiro
Abstract Immobilized nickel catalysts SBA*‐L‐x/Ni (L=bis(2‐pyridylmethyl)(1H‐1, 2, 3‐triazol‐4‐ylmethyl)amine) with various ligand densities (L content (x)=0.5, 1, 2, 4 mol % Si) have been prepared from azidopropyl‐functionalized mesoporous silicas SBA‐N3‐x. Related homogeneous ligand 2 and its NiII complexes, [Ni(2)(OAc)2(H2O)] (2/Ni) and [Ni(2)2]BF4 (2 2/Ni), have been synthesized. The L/Ni ratio (0.9–1.7:1) in SBA*‐L‐x/Ni suggests the formation of an inert [NiL2] site on the surface at higher ligand loadings. SBA*‐L‐x/Ni has been applied to the catalytic oxidation of cyclohexane with m‐chloroperbenzoic acid (mCPBA). The catalyst with the lowest loading shows high activity in its initial use as the homogeneous 2/Ni catalyst, with some metal leaching. As the ligand loading increases, the activity and Ni leaching are suppressed. The importance of site‐density control for the development of immobilized catalysts has been demonstrated.